PENGARUH PRODUK WISATA DAN ELECTRONIC WORD OF MOUTH (EWOM) TERHADAP KEPUTUSAN BERKUNJUNG DAN MINAT BERKUNJUNG KEMBALI PADA PENGUNJUNG WISATA ALAM MAYANG DI KOTA PEKANBARU - ,Tengku Firli Musfar, Anggita Marissa Simatupang , Hj. Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the influence of tourism products and electronic word of wouth (eWOM) on visiting decisions and interest in visiting Alam Mayang in the city of Pekanbaru. Primary data were collected through questionnaires. The type of research used is explanatory with a quantitative approach. The population in this study includes visitors or who have visited Alam Mayang tourism and in accordance with certain criteria with a sample of 100 respondents. Data was collected through the distribution of questionnaires and then the data was processed by path analysis using SPSS version 25. The results showed that tourism products and electronic word of mouth (eWOM) had a significant effect on the decision to visit and interest in visiting  back Alam Mayang tourism visitors in the city of Pekanbaru either directly or indirectly and the decision to visit also had a significant effect on the interest in visiting back Alam Mayang tourism visitors in the city of Pekanbaru. Keywords: Travel Products, electronic Word of Mouth (eWOM), Visiting Decision, Interest in Visiting Back